Constitutional organization of Switzerland experiences and lessons - Novičić Žaklina (Međunarodni Problemi, 2002)
The subject of this article is the constitutional organization of Switzerland, based on the current constitution adopted in April 1999. After the brief historical background and presentation of the principal features of the Swiss political community the author analyses the following constitutional arrangements: organization of the federal authority relationship between the federation and cantons, the role and functioning of the local government and political rights of Swiss citizens. The application of this arrangement in practice, with international status of neutrality special political culture that cherishes compromises and coalitions, idea of a nation as a political, not ethnical community and economic wealth, have contributed, in the author's opinion, to the stability of the Swiss highly complex political system.